2021
DOI: 10.1038/s41467-021-20907-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of DNA methylome from precancerous lesions to invasive lung adenocarcinomas

Abstract: The evolution of DNA methylome and methylation intra-tumor heterogeneity (ITH) during early carcinogenesis of lung adenocarcinoma has not been systematically studied. We perform reduced representation bisulfite sequencing of invasive lung adenocarcinoma and its precursors, atypical adenomatous hyperplasia, adenocarcinoma in situ and minimally invasive adenocarcinoma. We observe gradual increase of methylation aberrations and significantly higher level of methylation ITH in later-stage lesions. The phylogenetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…Recent studies have observed congruent genomic and DNAm evolutionary trajectories in lung cancer [ 82 , 201 ] as well as other cancers [ 202 , 203 ], highlighting the potential for epigenetic changes to provide a milieu for genomic changes driving tumorigenesis. Integrating the genomic and epigenomic profiles of lung cancer in future studies is essential to better comprehend lung tumor evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have observed congruent genomic and DNAm evolutionary trajectories in lung cancer [ 82 , 201 ] as well as other cancers [ 202 , 203 ], highlighting the potential for epigenetic changes to provide a milieu for genomic changes driving tumorigenesis. Integrating the genomic and epigenomic profiles of lung cancer in future studies is essential to better comprehend lung tumor evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Daskalos et al demonstrated that increased hypomethylation of retrotransposable elements (LINE-1 and Alu) leads to their enhanced transcription and strongly correlates with increased genomic instability in NSCLC [ 81 ]. In concordance, increased global hypomethylation is also associated with higher mutation, copy number variation, and allelic imbalance burden, as well as Treg/CD8 ratio during lung cancer progression [ 82 ]. These results imply the potential role of DNA hypomethylation in increased chromosomal instability, mutagenesis, and altered microenvironment.…”
Section: Dna Methylation Dysregulation In Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the G allele of rs2280059 SNP, which lies within the promoter of HSPH1, is able to increase its expression levels, leading to enhanced resistance of the cancer cells to treatment in patients with advanced non-small-cell lung cancer [71]. Apart from motif changes, CNVs may also alter the methylation status of oncogenic promoters (e.g., through the demise of methylation sites) leading to increased proliferation advantages for the mutated cell subpopulations, evidence of which have been extensively found in lung adenocarcinoma [124]. Collectively, genetic variability in promoter regions often associates with altered gene expression that links to disease progression of various cancer types.…”
Section: Genetic Variability In Promotersmentioning
confidence: 99%
“…Epigenomic studies have shown that tumors with MSI exhibit hypermethylation of key genes implicated in tumor development ( 75 , 86 ). The hypermethylated promoters were identified in some genes that regulate some main molecular signaling cascades ( 75 , 76 , 87 ): WNT (in the absence of WNT-signals, β -catenin—a key downstream effector of this pathway—is targeted for degradation through phosphorylation; the WNT signals thus stabilize the intracellular levels of β -catenin and subsequently increase transcription of downstream target genes in many human cancers), hedgehog (essential for embryonic and postnatal development, this pathway remains in the quiescent state in adult tissues but gets activated upon inflammation and injuries), and PTEN (its inactivation through mixed genetic/epigenetic mechanisms results in persistent activation of PI3K effectors, with an important impact on cell proliferation, apoptosis resistance, angiogenesis, metabolism regulation, genomic instability, cellular senescence, and cell migration).…”
Section: Genetic Instabilitymentioning
confidence: 99%